Islam in Provincial Indonesia: Middle Class, Lifestyle, and Democracy - Noorhaidi Hasan (Al-Jami'ah: Journal of Islamic Studies, 2011)
Islamic symbols have flourished in the public spaces of Indonesian provincial towns after Suharto. This phenomenon has occurred in parallel with the  significant shifts in the social, economic and political fields, which is tied to the mounting impact of Islamization, social mobility, economic growth, and democratization occurring among town people. It is as if we see a parallel move between Islamization, modernization, globalization and democratization. Key concepts associated with these trends are appropriated with those rooted in tradition and local culture to inform the whole dynamics of Indonesian provincial towns today. The key player in this process is the new middle class, who look to Islam for inspiration both to claim distinction and social status and to legitimize their consumptive lifestyle. They are newly pious who act as active negotiators between the global and the local as well as the cosmopolitan centre and the hinterland. They also play a pivotal role as an agency that liberalizes religion from its traditionally subservient, passive and docile posture by turning it into a source of moral legitimacy and distinction to represent a modern form of life. Given its intimate relationship with locality, tradition, modernity as well as globalization, Islam has increasingly assumed a greater importance for local politics. Political elites have used Islamic symbols for the instrumental purpose of extending their political legitimacy and mobilizing constituency support, in a political environment of open competition and increased public participation in decision making. In this process religious symbols have irrefutably been distanced from their religious moorings and narrow, Islamist understandings, in favor of pragmatic political purposes.